Association of deficits in short-term learning and Aβ and hippocampal volume in cognitively normal adults. (3rd November 2020) - Lim, Yen Ying; Baker, Jenalle E.; Bruns, Loren; Mills, Andrea; Fowler, Christopher; Fripp, Jurgen; Rainey-Smith, Stephanie R.; Ames, David; Masters, Colin L.; Maruff, Paul
Abstract : Objective: To determine the extent to which deficits in learning over 6 days are associated with β-amyloid–positive (Aβ+) and hippocampal volume in cognitively normal (CN) adults. Methods: Eighty CN older adults who had undergone PET neuroimaging to determine Aβ status (n = 42 Aβ− and 38 Aβ+), MRI to determine hippocampal and ventricular volume, and repeated assessment of memory were recruited from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. Participants completed the Online Repeatable Cognitive Assessment–Language Learning Test (ORCA-LLT), which required they learn associations between 50 Chinese characters and their English language equivalents over 6 days. ORCA-LLT assessments were supervised on the first day and were completed remotely online for all remaining days. Results: Learning curves in the Aβ+ CN participants were significantly worse than those in matched Aβ− CN participants, with the magnitude of this difference very large ( d [95% confidence interval (CI)] 2.22 [1.64–2.75], p < 0.001), and greater than differences between these groups for memory decline since their enrollment in AIBL ( d [95% CI] 0.52 [0.07–0.96], p = 0.021), or memory impairment at their most recent visit. In Aβ+ CN adults, slower rates of learning were associated with smaller hippocampal and larger ventricular volumes. Conclusions: These results suggest that in CN participants, Aβ+ is associated more strongly with a deficit in learning than any aspect of memory dysfunction. Slower rates of learning in Aβ+ CN participants were associated with hippocampal volume loss. Considered together, these data suggest that the primary cognitive consequence of Aβ+ is a failure to benefit from experience when exposed to novel stimuli, even over very short periods.